1928
DOI: 10.1172/jci100203
|View full text |Cite
|
Sign up to set email alerts
|

Temporary and Permanent Myxedema Following Treated and Untreated Thyrotoxicosis 1

Abstract: Although myxedema following treatment for toxic goiter has been reported frequently before, we wish to call attention to certain of its aspects which we regard as particularly worthy of emphasis, viz., (a) the existence of two types-temporary and permanent, (b) the rarity of the permanent type, (c) its late onset after x-ray therapy, (d) its occurrence following untreated toxic goiter. The permanent type will be considered first. I. PERMANENT MYXEDEMA FOLLOWING TREATED THYROTOXICOSISA. Rarity In the pioneer da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1928
1928
1974
1974

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…These 27 cases provide the material for this article. The 3 others, dealt with in the article on myxedema following thyrotoxicosis (2), had signs and symptoms suggestive of mild thyroid deficiency coincident with their period of temporary low metabolism, but later were symptom-free, although they again developed a low metabolism which as yet has not proved to be of the temporary type.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These 27 cases provide the material for this article. The 3 others, dealt with in the article on myxedema following thyrotoxicosis (2), had signs and symptoms suggestive of mild thyroid deficiency coincident with their period of temporary low metabolism, but later were symptom-free, although they again developed a low metabolism which as yet has not proved to be of the temporary type.…”
Section: Methodsmentioning
confidence: 99%
“…2 Sections 2 and 3 are dealt with in subsequent papers (1) (2). This paper is devoted to a study of the temporary type of low metabolism without myxedema, with special reference to the r6le that iodine therapy plays in its production.…”
Section: Introductionmentioning
confidence: 99%
“…Radioiodine uptake (42) and scintiscan (43) studies have shown that a nodule with decreased creased function is four times more likely to contain a malignant tumor. Scanning may show that some benign thyroid lesions (such as nontoxic adenomatous nodules, cysts, thyroiditis, fibrosis or calcification) are functioning at a low level or not at all (11, 12, 18). Meadows (43) reported carcinoma in 58 per cent of so‐called “cold” nodules but in only 4.7‐6.6 per cent of “hot,” “warm” and “cool” nodules.…”
Section: Clinical Diagnosismentioning
confidence: 99%
“…4 It is our purpose in this paper to present a study of permanent low metabolism without myxedema. The data on temporary and permanent myxedema following thyrotoxicosis, are to be presented later (2). 0 Although there are a few reports in the literature on low metabolism without myxedema, there are no studies of this phenomenon foHlowing thyrotoxicosis.…”
Section: Introductionmentioning
confidence: 99%